Analysis of Service Response Time at Outpatient Polyclinic at Regional General Hospital (RSUD) S.K. Lerik, Kupang - Purba, Sondang; Marni, Marni; Mado, Fransiskus G.; Nayoan, Christina R.; Littik, Serlie K. A. (Jurnal Pangan Gizi dan Kesehatan, 2026)
Background: Hospitals are institutions that provide comprehensive individual health services. To ensure quality and continuous improvement of these services, hospitals are guided by regulations issued by the Ministry of Health. One key indicator of service quality is patient waiting time at outpatient clinics. Objectives: This study aims to explore several factors affecting service quality at the outpatient polyclinic of RSUD S.K. Lerik, Kupang. These factors include response time of health and non-health workers, hospital budget allocation, worker competence, availability of essential documents, and the overall service flow mechanism. Methods: This qualitative study applied a management theory approach and was conducted at RSUD S.K. Lerik, Kupang. Data were collected from eight informants selected through purposive sampling. Results: The Results of the study showed that that although the response time of health and non-health workers and the availability of service flow mechanisms are relatively good, there are still several challenges. The number of personnel remains limited, and there is no specific budget allocated to the outpatient clinic; instead, needs are recorded and submitted to hospital management. Equipment and materials such as computers and network systems are available, but often insufficient, especially in urgent situations. Despite these limitations, the flow of services generally proceeds without major delays. Conclusions: It is recommended that hospital officers ensure timely service delivery according to established standards to minimize patient waiting times. Improving the management system and increasing attention to service response time in outpatient clinics can help enhance the quality, safety, and comfort of healthcare services provided.